Patient's freedom and informed consent in Nigeria: a symbiotic relationship (2017)
The fundamental rights of a patient to freedom or autonomy and informed consent are two symbiotic concepts that regulate the relationship between a doctor and a patient. A patient's right-to-know and determine his health issues is not just ethical principles but legal obligations of a doctor to his patient which increases the latter's confidence in his doctor and the entire health-care team. Although both rights are independent, they are also symbiotic in nature; and the enjoyment of one right results in the enjoyment of the other while the deprivation of one causes the denial of the other. Therefore, this article shall examine the dual concepts of autonomy and informed consent; the limitations and exceptions to the doctrine of informed consent; the symbiotic relationship between a patient's autonomy/freedom and informed consent, and conclude by recommending how the symbiotic relationship between both concepts can be strengthened and enjoyed better in Nigeria